Anti-Diabetic Herbo-Mineral Drugs From Priya Nighantu (AYUSHDHARA, 2024)
Ayurveda is the science of life mainly targets for Swasthasya Swathya Rakshanam and Aturasya Vikara Prashamanamcha i.e., maintaining the healthy state of the healthy person and treating the diseased person. Prameha is not a new challenge for Ayurveda, rather it’s a challenge for new generation following principles. Diabetes mellitus, a metabolic disease, is found to have much similarity with Prameha. Diabetes mellitus is a major health problem for the world in the 21st century. About 537 million adult were living with diabetes in 2021 according to IDF Diabetes Atlas and this number expected to raise upto 643 million by 2030 and 783 million by 2045. To get rid of this burning problem of society, we compiled some single effective and safe herbo-mineral remedy to control diabetes. Plants are the exclusive source of the drugs for the treatment of various ailments. Now days millions of people are dependent upon herbal medicines. Acharya Priyavrat sharma in his Priya nighantu describes various herbo-mineral drugs act upon Prameha (diabetes). Many treatment modalities mentioned in different Ayurvedic lexicon for Prameha. The present review study focus to screen drugs acting on Prameha (diabetes). 41 Dravya out of total 643 Dravya are described with Pramehahara property throughout the lexicon which includes herbal, mineral and food origin.